Novel femoral head allograft reconstruction technique of giant cell tumor of the bone in the mid-foot: a case report - Rahimzadeh, Jason; Singh, Rohan; Biron, Dustin; Para, Ashok; Ippolito, Joseph; Lin, Sheldon; Benevenia, Joseph (International Journal of Research in Orthopaedics, 2026)
An 83-year-old female presented with seven months of right medial foot swelling. Imaging revealed a lesion of the medial and middle cuneiforms with extension into the 1st and 2nd metatarsals. Biopsy suggested giant cell tumor of bone. She underwent wide excision, argon beam adjuvant, and reconstruction with a custom-molded femoral head allograft and midfoot arthrodesis. At one-year follow-up, she was pain-free, weight-bearing, and demonstrated fusion without recurrence. This case highlights a novel cement-mold technique to optimize graft fit, introducing a reconstructive strategy that maintains midfoot function despite extensive resection.